2020
DOI: 10.1002/jcla.23581
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the analytical performance of endocrine analytes using sigma metrics

Abstract: Background (a) To evaluate the clinical performance of endocrine analytes using the sigma metrics (σ) model. (b) To redesign quality control strategies for performance improvement. Methods The sigma values of the analytes were initially evaluated based on the allowable total error (TEa), bias, and coefficient of variation (CV) at QC materials level 1 and 2 in March 2018. And then, the normalized QC performance decision charts, personalized QC rules, quality goal index (QGI) analysis, and root causes analysis (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 30 publications
(61 reference statements)
4
10
0
Order By: Relevance
“…According to the equation Sigma = (TEa% ‐ Bias%)/CV%, significantly different σ values are obtained using the same Bias% and CV% but different total allowable error targets similar to the previous studies, 10,11 the greater the TEa is, the greater the Sigma value is. In this study, initially five different TEa targets were included.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…According to the equation Sigma = (TEa% ‐ Bias%)/CV%, significantly different σ values are obtained using the same Bias% and CV% but different total allowable error targets similar to the previous studies, 10,11 the greater the TEa is, the greater the Sigma value is. In this study, initially five different TEa targets were included.…”
Section: Discussionsupporting
confidence: 71%
“…Further the Sigma Method Decision Charts were constructed in terms of TEa NCCL , providing us with a visual view of the analytes’ performance. For analytes with σ<6, the cause for poor performance was evaluated using QGI similar to previous studies 10,11 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the performance specifications of urinary biochemical analytes have no data about biological variation, so we selected a quality goal of urinary bio- Previous studies have shown that the six sigma model has been widely used to evaluate the analytical performance of serum biochemical markers, immunological markers, and other analytes and to guide laboratories in designing risk-based SQC strategies and improvement measures. [18][19][20][21][22] However, the application of six sigma models in urinary biochemical analytes is rare at present. Therefore, we aimed to use the six sigma model to evaluate the analytical performance of urinary biochemical analytes across five laboratories, design risk-based SQC strategies and quality improvement measures, and provide more accurate and reliable analytical results for clinical application.…”
Section: Introductionmentioning
confidence: 99%